2023
DOI: 10.22541/au.167535214.41739207/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-cell-density production of adeno-associated viral vector serotype 6 by triple transfection in suspension HEK293 cell cultures

Abstract: The use of adeno-associated viruses (AAV) as vectors for gene and cell therapy has risen considerably in recent years. Consequently, the amount of AAV vectors required during the validation and clinical trials has also increased. AAV serotype 6 (AAV6) is well-documented for its efficiency in transducing different cell types and has been successfully used in gene and cell therapy protocols. However, the number of vectors required to effectively deliver the transgene to one single cell has been estimated at 106 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 78 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…[47,48] Enhancing cellular metabolism through process optimization may elevate rAAV productivity. [49,50] Our synthetic cell lines included only a minimal set of AAV and helper genes. While productivity achieved has been good, it is possible that additional helper viral genes, such as E4orf6/7 and others, which modulate host cell functions like DNA replication, cell cycle progression, and DNA repair, could aid in virus genome replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47,48] Enhancing cellular metabolism through process optimization may elevate rAAV productivity. [49,50] Our synthetic cell lines included only a minimal set of AAV and helper genes. While productivity achieved has been good, it is possible that additional helper viral genes, such as E4orf6/7 and others, which modulate host cell functions like DNA replication, cell cycle progression, and DNA repair, could aid in virus genome replication.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47,48 ] Enhancing cellular metabolism through process optimization may elevate rAAV productivity. [ 49,50 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilized a previously published dataset [19] to developed a metabolic model framework based on flux kinetics related to AAV production in the HEK293 cell line platform.…”
Section: Experiments Data Setsmentioning
confidence: 99%
“…However, since such information is only available for five of the species, adjustments to the initial concentration of the remaining species, as well as the model parameters, were made during the optimization iterations. Further details about this real-world example can be found in another source [19].…”
Section: Experiments Data Setsmentioning
confidence: 99%
“…Adeno-associated virus (AAV) vectors are increasingly being used in gene therapy because of their safety, diverse tropism, sustained expression, and ability to effectively infect both dividing and nondividing cells. [1][2][3][4][5] To date, six AAV-based gene therapies have been approved for clinical use by regulatory agencies and more than 255 clinical trials have been conducted or are ongoing. [6] To date, more than 100 AAV serotypes, including synthetic serotypes, have been identified that exhibit various tropisms and characteristics in human tissues.…”
Section: Introductionmentioning
confidence: 99%